Albania, the Right-to-not be Treated, and COVID-19 (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This paper studies the right-to-not be treated in conjunction with the Albanian legislation during the time of a pandemic situation. Although the current Albanian legislation might consider withholding or withdrawing treatment from an unconscious patient as a criminal offense, in the existing pandemic situation, the application of the ethical principle of justice concludes in the key result of not punishing physicians. Therefore, in these cases even in the absence of specific rules governing end-of-life decisions, physicians should not be liable for criminal offenses.
Keywords: Albania; Criminal Law; Right not to be treated; CoViD-19; principle of justice